(untitled) (Development Service Industry Management, 2023)
Jeep tourism and active recreation are becoming more and more popular in many countries, including Ukraine. In recent years, there has been an increase in interest in adventure and extreme types of recreation, in particular, such as jeeping. The increase in the number of tourists who are interested in jeeping actually contributes to the economic growth of the country, but also the emergence of problems related to issues in the natural environment. The aim of the study is coverage of the main problems and trends in the development of jeep tourism in Ukraine. The object of research is jeep tourism in Ukraine. The subject of research is global and domestic experience and prospects for the development of jeep tourism The article explores the fundamental concept of jeep tourism, its various types, and its place within the overall structure of tourism. The section also highlights the unique characteristics of organizing jeep tours. The second part of research delves into the history of the emergence of jeep tourism both globally and in Ukraine. It explores international experiences in organizing jeep tourism and discusses the experiences of Ukraine in organizing such tours, including the involvement of jeep enthusiasts’ associations and tour companies offering this type of adventure. The main problems associated with the development of jeep tourism in Ukraine have been analyzed. This includes examining the environmental impact of jeep tourism on flora, fauna, and soil. Additionally, other negative aspects of implementing jeep tours are considered. The section also addresses the legal and organizational regulations concerning jeep tourism in Ukraine and concludes with proposals for enhancing and developing jeep tourism in the country. This research provides valuable insights into the various dimensions of jeep tourism, its development, and the challenges it faces in Ukraine. The findings can be beneficial for tourism organizations, government institutions, and other stakeholders in the tourism industry, as well as environmental conservation efforts.